AB0652 Clinical Experience with Biological Therapy in Large Vessel Arteritis. (9th June 2015) - Vinicki, J.P.; Arredondo, M.; Humbría, A.; Garcia-Vicuña, R.; Lopez-Bote, J.P.; Garcia-Vadillo, A.; García-Arias, M.; Castañeda Sanz, S.; Alvaro-Gracia, J.M.
Abstract : Background: Most patients with giant cell arteritis (GCA) and/or Takayasu arteritis (TA) have a chronic disease that requires long-term treatment with glucocorticoids (GC). Adverse events (AEs) secondary to GC, along with a high rate of relapses (>50%) have encouraged the search for alternative treatments such as biological therapies (BT). Objectives: To describe the results obtained in clinical practice with the use of BT in patients diagnosed with TA and GCA. Methods: TA and GCA patients who received BT (infliximab [IFX], etanercept [ETN] and tocilizumab [TCZ]) were included. We analyzed treatment information (previous and current) with clinical response during 24 months, last follow-up, revascularization procedures and relevant AEs. In TA, active disease was defined according to Kerr Criteria. In GCA, active disease was defined according to similar modified criteria. In case of no active disease, the patient was considered in remission. Numerical data are expressed as mean and standard deviation (SD) for continuous variables and percentages for qualitative variables. Results: Ten patients were included (Table 1 ). The median time of disease duration was similar in both groups (10.6±6.3 years), the main reason for starting BT was lack of response to prior therapy (MTX, LEF, MMF, AZA and CYC) and/or ≥2 relapses during GC tapering. Five patients started IFX, four TCZ and 1 ETN. In TA, the remission was observed before 6 months (n=5) and in GCA, before 3 (n=4) and 6 months (n=1). No patient had relapses during follow-up (mean follow-up 37.8±31.9 months) and the daily dose of GC was reduced by 70%. Two AEs were attributable to IFX (recurrent infections and anaphylaxis) and 1 AE attributable to TCZ (mild neutropenia). At last follow-up, 5 patients continued with BT, 1 patient discontinued BT for sustained remission (ETN), 1 patient was lost to follow up (moved to another country), 2 patients discontinued BT secondary to AE attributable to IFX and 1 patient died for reasons not attributable to BT. Conclusions: We observed a favorable response to BT in patients with TA and GCA. Thus, BT might be considered as an alternative in patients with large vessel arteritis refractory to conventional treatment or with GC related comorbidities. Disclosure of Interest: None declared